Kesetaraan Gender dalam Persfektif Islam - Ilfa Harfiatul Haq (Institut Agama Islam Negeri Padangsidimpuan, 2019)
There is a negative stigma which assumes that Islam does not respect the position of women, limits its freedom, is unjust and makes women a second-class human being under the control of men. These reasons make this writing is interested. Departing from that thought, they also considered that Islam was the main obstacle to the struggle for gender equality. The purpose of this study is to uncover the core problem of gender equality in an Islamic perspective. This research was conducted using Islamic study methods and approaches. The position of women in Islam has the same rights and obligations as men, although there are some things that women cannot do and men can do, and vice versa. As for what distinguishes the degree between men and women is the level of piety. Islam has far raised the status of women and it can be said that in other religions there is nothing like and even exceeding the privileges of women other than in Islam.